2022
DOI: 10.1590/1806-9282.20220216
|View full text |Cite
|
Sign up to set email alerts
|

“Zooming” in strategies and outcomes for trauma cases with Injury Severity Score (ISS) ≥16: promise or passé?

Abstract: OBJECTIVE:Rescuing severe trauma cases is extremely demanding. The present study purposed to analyze the efficiency of trauma management at Emergency Centre, University Clinical Centre of Serbia, Belgrade, included outcome within 28 days. METHODS: This retrospective study involved 131 intensive care unit trauma cases with total Injury Severity Score ≥16, in terms of administrating the two strategies: (i) definitive surgical repair and (ii) damage control laparotomy. RESULTS: The damage control laparotomy cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…histopathologically [16]. Therefore, emergency surgery remains significant and critical, globally, in severe cases [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…histopathologically [16]. Therefore, emergency surgery remains significant and critical, globally, in severe cases [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…de Wijkerslooth et al [25] concluded that same-day discharge after LApp for uncomplicated appendicitis is safe without an augmented risk of readmission, complications, or unplanned hospital visits. As a matter of fact, emergency surgery remains significant and severe globally in the mentioned era [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The data from each patient were input into a Microsoft Excel (Microsoft Corporation, Redmond, WA, USA) chart, and data analysis was conducted on a personal computer using statistics software (SPSS for Windows, version 23.0; SPSS, Chicago). The relevant injuries in six categories were examined with regard to three age groups (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and 65 years and older) and four different imaging intervals (<24, 24-48, 49-72, and >72 h) (Figure 1). The Pearson χ 2 test was used in order to determine the differences associated with the age groups and imaging intervals in the involved body parts.…”
Section: Discussionmentioning
confidence: 99%